PYTEXLIB – OPEN SOURCE PYTHON LIBRARY FOR SCRIPTING TEXTILE STRUCTURES - Kyosev, Yordan; Naake, Anselm; Schmidt, Ann-Malin (Fibres and Textiles, 2025)
This work presents a small, minimalistic, pure Python based open source library, which was designed to simplify the parametric creation of textile structures. The library comes as result of long years of teaching modelling of textiles at master and PhD level, where the difficulties with all existing packages and the learning outcomes from such one course were considered. The idea of the library is that the students learn at the same time first steps of programming Python using small library, it is running on any operation system and from other point of view, the user is able to concentrate on the textile architecture, not getting lost in the coding style, data structures etc. PyTexLib is used since 4 years successful in the education at TU Dresden and in WE-TEAM program and is available as open source at GitHub.